THE EFFECT OF AUDIT TENURE, AUDIT FEE, CLIENT COMPANY SIZE, MANAGERIAL OWNERSHIP , AND KAP REPUTATION ON AUDIT QUALITY : A STUDY OF CONSUMER CYCLICAL AND CONSUMER NON CYCLICAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Sari, Riskia Naralita; Alit Triani, Ni Nyoman (LPPM Universitas Bina Bangsa, 2025)
This study aims to prove the influence of audit tenure, audit fee, company size, managerial ownership, and KAP reputation on audit quality. This study uses secondary data in the form of annual reports. Sampling using a purposive sampling technique which produces a total of 107 data from Consumer Cyclical and Consumer Non-Cyclical companies over a period of 2 years, with a total of 214 observations. The data analysis used in the study is multiple linear regression analysis. Audit quality measurement uses the Discretionary Accruals Modified Jones Model (1995). The results of this study indicate that audit fees have a positive effect on audit quality, while firm size has a negative effect on audit quality. Meanwhile, audit tenure, managerial ownership, and KAP reputation do not affect audit quality.